2014
DOI: 10.1186/preaccept-9361627801386224
|View full text |Cite
|
Sign up to set email alerts
|

Altered lipid levels provide evidence for myelin dysfunction in multiple system atrophy

Abstract: Multiple system atrophy (MSA) is a rapidly-progressive neurodegenerative disease characterized by parkinsonism, cerebellar ataxia and autonomic failure. A pathological hallmark of MSA is the presence of α-synuclein deposits in oligodendrocytes, the myelin-producing support cells of the brain. Brain pathology and in vitro studies indicate that myelin instability may be an early event in the pathogenesis of MSA. Lipid is a major constituent (78% w/w) of myelin and has been implicated in myelin dysfunction in MSA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…In both PD and MSA models, genes related to the regulation of lipid metabolism were affected upon SNCA overexpression. These data support the role of α-synuclein (of either neuronal or oligodendroglial origin) in the modulation of brain lipid turn-over as shown in human PD [ 79 ; 80 ] and MSA [ 62 ]. Finally, regulation of apoptosis (GO:0042981) was significantly associated with the disease processes in the striatum of both PD and MSA mice.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…In both PD and MSA models, genes related to the regulation of lipid metabolism were affected upon SNCA overexpression. These data support the role of α-synuclein (of either neuronal or oligodendroglial origin) in the modulation of brain lipid turn-over as shown in human PD [ 79 ; 80 ] and MSA [ 62 ]. Finally, regulation of apoptosis (GO:0042981) was significantly associated with the disease processes in the striatum of both PD and MSA mice.…”
Section: Discussionsupporting
confidence: 83%
“…Of note, genes with links to lipid metabolism, such as Pdk4 (Pyruvate Dehydrogenase Kinase, Isozyme 4), Lpl (Lipoprotein Lipase) or Pla2g4e (Phospholipase A2, Group IVE) were strongly represented in this group ( Fig 7B ). Changes in lipid metabolism have been shown to be relevant to the human disease [ 62 ], and it is therefore intriguing to see that early alterations in this process might be caused by miRNA-mRNA network interactions. The module “Transmembrane transport” was a further category with prominent predicted interaction between dysregulated miRNAs and mRNAs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Changes to microRNA-96 resulted in downregulation of the solute carrier protein family SLC1A1 and SLC6A6 [ 23 ]. Myelin instability is regarded as an early event in MSA pathogenesis and a recent study showed that the myelin lipids (sphingomyelin, sulfatide and galactosylceramide) were severely decreased in MSA white matter specifically in disease-affected regions, providing further clues to MSA pathogenesis [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%